HIV-1 strains belonging to large phylogenetic clusters show accelerated escape from integrase inhibitors in cell culture compared with viral isolates from singleton/small clusters. (2nd May 2017) - Brenner, Bluma G.; Ibanescu, Ruxandra-Ilinca; Oliveira, Maureen; Roger, Michel; Hardy, Isabelle; Routy, Jean-Pierre; Kyeyune, Fred; Quiñones-Mateu, Miguel E.; Wainberg, Mark A.; ,
Abstract: Objectives: Viral phylogenetics revealed two patterns of HIV-1 spread among MSM in Quebec. While most HIV-1 strains ( n  =   2011) were associated with singleton/small clusters (cluster size 1–4), 30 viral lineages formed large networks (cluster size 20–140), contributing to 42% of diagnoses between 2011 and 2015. Herein, tissue culture selections ascertained if large cluster lineages possessed higher replicative fitness than singleton/small cluster isolates, allowing for viral escape from integrase inhibitors. Methods: Primary HIV-1 isolates from large 20+ cluster ( n  =   11) or singleton/small cluster ( n  =   6) networks were passaged in vitro in escalating concentrations of dolutegravir, elvitegravir and lamivudine for 24–36 weeks. Sanger and deep sequencing assessed genotypic changes under selective drug pressure. Results: Large cluster HIV-1 isolates selected for resistance to dolutegravir, elvitegravir and lamivudine faster than HIV-1 strains forming small clusters. With dolutegravir, large cluster HIV-1 variants acquired solitary R263K ( n  =   7), S153Y ( n  =   1) or H51Y ( n  =   1) mutations as the dominant quasi-species within 8–12 weeks as compared with small cluster lineages where R263K ( n  =   1/6), S153Y (1/6) or WT species (4/6) were observed after 24 weeks. Interestingly, dolutegravir-associated mutations compromised viral replicative fitness, precluding escalations in concentrations beyond 5–10 nM. With elvitegravir, large cluster variants more rapidly acquired first mutations (T66I, A92G, N155H or S147G) by week 8 followed by sequential accumulation of multiple mutations leading to viral escape (>10 μM) by week 24. Conclusions: Further studies are needed to understand virological features of large cluster viruses that may favour their transmissibility, replicative competence and potential to escape selective antiretroviral drug pressure.